Between Do’s and Don’ts in the Catching-Up Process – Lessons for Romania from the Eu-15 Cohesion Countries - Marius PROFIROIU; Victor Romeo IONESCU; Daniela Luminița CONSTANTIN; Gabriela MARCHIȘ (Transylvanian Review of Administrative Sciences, 2009)
This papers aims to examine the experienceof the four “Cohesion Countries” of the EU-15– Ireland, Spain, Portugal and Greece and toidentify their best practices as well as a seriesof drawbacks in the implementation of the EUstructural assistance. The resulted conclusionscan be taken as useful lessons for the EU’s NewMember States with regard to their efforts to absorbthe EU funds and to reduce the discrepanciesbetween their development level at national andregional scale and the EU average (the so-called“catching-up” process). A special emphasis willbe put on the case of Romania, considering theauthors’ research results in this field and theirrecent calculations focused on the absorption ofthe pre-accession funds, especially the Phareassistance. Their findings will be the source ofseveral considerations and proposals for increasingRomania’s absorption capacity in the 2007-2013programming period.